Falha de Encke : mapa de difusão - Vieira, Júlia Torello [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The Encke Gap is located in Saturn’s A ring at 133584km from the planet. It contains the satelite Pan and an internal ring system including the inner ring, outer ring, central ring and fourth ring, located at 133484km, 133720km, 133584km and 133584km from Saturn’s center. In this work we will define diferent dinamical regimes present when a satellite is immersed in a planetery ring: chaos, horseshoe orbit and waves. We will also do numerical simulations aiming at reproducing the dinamical system of the Encke Gap, and conclude that the regions of chaos and horseshoe orbit occur at 111.64km and 25.76km from Pan, respectively. A diffusion map will be used to check the stability of the rings inside the Encke Gap. The central ring is the most stable since it shares its orbit with Pan in the horseshoe region. The inner ring and the fourth ring are in the chaotic region of the gap and are very unstable presenting log D = −2. We will also see that the outer ring is unstable with log D = −3 despite being outside the chaotic region.

A Falha de Encke está localizada no anel A de Saturno a uma distância de 133584km do planeta. Ela contem o satélite Pan e um sistema de anéis internos, que são: anel interno, anel externo, anel central e quarto anel; às distâncias de 133484km, 133720km, 133584km e 133680km de Saturno. Nesse trabalho de conclusão de curso deﬁniremos os diferentes regimes dinâmicos presentes quando um satélite é imerso em um anel: caos, ferradura e ondas. Realizaremos simulações numéricas com o objetivo de reproduzir o sistema dinâmico da Falha de Encke e veriﬁcaremos que as regiões de caos e ferradura ocorrem até 111.64km e 25.76km de Pan, respectivamente. Um mapa de difusão foi usado na veriﬁcação da estabilidade dos anéis presentes no interior da falha. O anel central é o mais estável dos quatro anéis por dividir órbita com Pan em região de ferradura. O anel interno e quarto anel estão localizados em região de caos e apresentam log D = −2. Apesar do anel externo estar fora da região caótica, ele também tem difusão alta (log D = −3).
Encke gap : diffusion map
Keywords: Orbital dynamics; Planetary rings; Numerical simulation; Dinâmica orbital; Anéis planetários; Simulação numérica; Satélites artificiais; Planetas - Órbitas; Saturno (Planeta); Mecânica celeste